Modification of Soils used in the Construction and Reconstruction of Slime Storage Dikes of Republican Unitary Enterprise Production Association (RUE PA) «Belaruskaliy» - B. A. Bogatov; G. A. Kooptel; F. G. Khaliaukin (Наука и техника, 2003)
The paper gives results of the investigations pertaining to modification of soils used in the construction and reconstruction of slime storage dikes of RUE PA «Belaruskaliy»